Gender and Discourse. - Tannen, Deborah (Oxford University Press, 1994)
Deborah Tannen's You Just Don't Understand has been on the New York Times Best Seller list for more than three years (in cloth and paper) and has sold over a million and a half copies. Clearly, Tannen's insights into how and why women and men so often misunderstand each other when they talk has touched a nerve. For years an internationally known and highly respected scholar in the field of linguistics, she has now become widely known for her work on how language both reflects and perpetuates the relationships between men and women. Her life work has demonstrated how close and intelligent analysis of conversation can reveal the extraordinary complexities of social relationships--including relationships between men and women. Now, in Gender and Discourse, Tannen has gathered together five of her scholarly essays--which provide a theoretical backdrop to her bestselling books--and an informative introduction which discusses her field of linguistics, describes the research methods she typically uses, and addresses the controversies surrounding her field as well as some misunderstandings of her work. (She argues, for instance, that her cultural approach to gender differences does not deny that men dominate women in society, nor does it ascribe gender differences to women's "essential nature.") The essays themselves cover a wide range of topics. In one, she analyzes a number of conversational strategies--such as interruption, topic raising, indirection, and silence--and shows that, contrary to much work on language and gender, no strategy leads inflexibly to dominance or submissiveness in conversation--interruption (or overlap) can be supportive, silence and indirection can be used to control. It is the interactional context, the participants' individual styles, and the interaction of their styles, Tannen shows, that result in the balance of power. She.